Building Materials and Structural Elements Special topic volume with invited peer-reviewed papers only - Almadny, Hussein Abdulmuttaleb; Alkhafaji, Ayad Kadhim; Al Asadi, Layth Abdul Rasool (Key Engineering Materials, 2021)
Collected papers reflect the modern view of researchers on creating environmentally friendly building materials and technologies and solving the problems associated with environmental safety to achieve sustainable development. Building Materials, Concrete, Cement, Asphalt, Mechanical Properties, Durability, Reinforcement, Mixture, Geotechnics, Pile, Foundation, Soil Shear Strength, Hydrology, Aquatic Resources, Irrigation Network, Water Treatment Materials Science, Building Materials, Bioscience and Medicine.